PID Controller Tuning Optimization Using Gradient Descent Technique For An Electro-Hydraulic Servo System - Chong, Chee Soon; Ghazali, Rozaimi; Jaafar, Hazriq Izzuan; Syed Hussien, Sharifah Yuslinda (Penerbit UTM Press, 2015)
The prominent performance of electro-hydraulic servo (EHS) system has received a positive admission in the industrial field. EHS system is well known to be disclosed to the parameter variations, disturbances and uncertainties which are affects by the changes in the operating conditions such as friction, internal and external leakage. The complexity and nonlinear characteristic of the EHS system leads to a great challenge in controller development and system modelling. The performance of the utilized controller can be improved in order to achieve its best capability. In this paper, the basic knowledge in optimization of the proportional-integral-derivative (PID) controller through Gradient Descent (GD) method was discussed. The PID parameters obtained through Ziegler-Nichols (ZN) tuning method has been optimized using the GD method via MATLAB/Simulink software. The findings illustrate significant improvement in the positioning tracking performance by applying the developed optimization technique. Therefore,the issues that were degraded the EHS system performance have been reduced.